ANALISIS KEBUTUHAN PENGEMBANGAN E-MODUL BIOLOGI BERBASIS SOLUSI PEMBELAJARAN MEDIA INTERAKTIF DI ERA PANDEMI - Ismi Nurul Qomariyah; Rudy Setiawan (Universitas Tribhuwana Tunggadewi, 2022)
This study aims to obtain initial data on the need to develop interactive media-based e-modules at the junior high school level, because of the need for a medium during the COVID-19 pandemic which has had a major impact on almost all sectors, including education which requires educators to be creative in developing learning resources, especially online learning resources. The method used in this research is descriptive qualitative by using several samples from all students of SMP/MTs in Malang, while the sample used includes 30 students of class IX in MTs. Al Itihad Poncokusumo, 30 Class IX students at SMPN 2 Tumpang, 15 students at SMP PGRI Tumpang Class IX and 15 Class IX students at SMPN 1 Jabung. Data collection techniques were carried out using observation, distributing questionnaires and interviews. Data were analyzed using descriptive analysis. The results of the needs analysis test showed that 93.57% of students stated that they felt they needed interesting learning media and could make it easier to understand the material with a score and 93.67% of students agreed that there was an e-module to facilitate learning. Meanwhile, all teachers agreed on the need to develop e-books, e-modules and other types of electronic teaching materials, so that online-based teaching materials are needed to support the learning process in the era of the COVID-19 pandemic. There is a need for the development of interactive media-based e-modules as a learning solution in the pandemic era. The results of this needs analysis test can be used as basic data for the development of interactive media-based e-modules.